Black women, writing, and identity: Migrations of the subject - Boyce Davies, Carole (Routledge, 1994)
Black Women Writing and Identity is an exciting work by one of the most imaginative and acute writers around. The book explores a complex and fascinating set of interrelated issues, establishing the significance of such wide-ranging subjects as: * re-mapping, re-naming and cultural crossings * tourist ideologies and playful world travelling * gender, heritage and identity * African women's writing and resistance to domination * marginality, effacement and decentering * gender, language and the politics of location Carole Boyce-Davies is at the forefront of attempts to broaden the discourse surrounding the representation of and by black women and women of colour. Black Women Writing and Identity represents an extraordinary achievement in this field, taking our understanding of identity, location and representation to new levels.
Keywords: approches et analyses; arts; discipline; fem1000; femmes* noires; féminismes noirs; littérature; premier cycle; ressource en ligne; thématiques; écriture des femmes*; études littéraires; études postcoloniales